2012
DOI: 10.1177/0095327x12437689
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating Army Exit

Abstract: There is recent concern about what becomes of Armed Forces leavers. This is most apparent among leavers themselves and is a feature of short careers that compel individuals to find replacement jobs and lifestyles. Concern for one's civilian future rises to prominence in the preexit period and is confronted in resettlement processes during this time. Based on qualitative analysis of interviews with twenty-eight UK regular Army career soldiers and officers, the article argues that the final year of service-thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 19 publications
3
34
0
1
Order By: Relevance
“…to 'failure' (which can include unemployment, homelessness and incarceration). Leavers are told to expect the return to civilian life to be 'stressful', and to require some 'personal adjustment' (British Army, 2018, no page), reflecting the fact that being in the military will inevitably have influenced the development of their identities (Cowen, 2005;Riley & Bateman, 1987;Walker, 2013). Extensive research has demonstrated that military veterans commonly experience 'significant cultural, social and spatial changes' (Herman & Yarwood, 2014, pp.…”
Section: Prisons As Spaces For Life Beyond the Militarymentioning
confidence: 99%
“…to 'failure' (which can include unemployment, homelessness and incarceration). Leavers are told to expect the return to civilian life to be 'stressful', and to require some 'personal adjustment' (British Army, 2018, no page), reflecting the fact that being in the military will inevitably have influenced the development of their identities (Cowen, 2005;Riley & Bateman, 1987;Walker, 2013). Extensive research has demonstrated that military veterans commonly experience 'significant cultural, social and spatial changes' (Herman & Yarwood, 2014, pp.…”
Section: Prisons As Spaces For Life Beyond the Militarymentioning
confidence: 99%
“…Two studies considered the value of military experience when preparing to leave. A descriptive qualitative study focused on the perceptions of British Army personnel who were leaving the military [10]. Participants generally described a naive attitude to civilian employment that was grounded in unrealistic or poorly informed assumptions about the superiority and usefulness of military experience in future civilian workplaces.…”
Section: Value Of Military Experiencementioning
confidence: 99%
“…Veterans exiting the military following a longer period of service were reported to fare better than early service leavers because they have adapted well to military life and have a firmer foundation upon which to launch their civilian careers [9]. However, those leaving the service following a longer career may hold an idealised view about the value of their previous military work experience and a naive view of civilian work [10]. Finally, military personnel are encouraged to hold values that include placing the needs of the military first and viewing their role as a service as opposed to a job [11].…”
Section: Introductionmentioning
confidence: 99%
“…Freddie reflected positively on the service life he gained from being in the Royal Marines: "the military made me who I am now and I think I'm a better person for it" (p. 32). An integrated sense of self, separate from how one defines self through career, is necessary for a feeling of satisfaction and thinking positively of the future (49). Mental health concerns and experiences of mental healthcare and support post-service were explored to understand to what degree (if any) participants linked postservice experiences to their current well-being and whether preor service events are integral to those perspectives which create conflicts in overall sense of well-being and coping with change after leaving the Armed Forces.…”
Section: Narrative Meaning-making and Evaluation Of Life After Servicementioning
confidence: 99%